Novel Advances in the Evaluation and Treatment of Children With Symptoms of Gastroesophageal Reflux Disease - Rosen, Rachel (Frontiers in Pediatrics, 2022)
Gastroesophageal reflux disease has long been implicated as a cause for multiple pediatric symptoms ranging from abdominal pain and regurgitation to cough and dental erosions. Diagnostic testing has evolved greatly over the last 20 years; initial testing with pH-metry to measure esophageal acid reflux burden has evolved into measurement of both acid and non-acid reflux and liquid and gas reflux. However, measuring reflux burden alone only tells a small part of the GERD story and many symptoms originally thought to be reflux related are, in fact, related to other disorder which mimic reflux. The current paradigm which involves empiric treatment of symptoms with acid suppression has been replaced with early testing for not only gastroesophageal reflux but also for other diagnostic masqueraders. The focus for interventions has shifted away from acid suppression towards motility interventions and includes a greater recognition of both functional and motility disorders which present with reflux symptoms.